PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP PENGEMBANGAN KARIER MELALUI KEPUASAN KERJA KARYAWAN PT. TASA TRITAMA UTAMA - Abdurrahman Jamil; Ismail Razak; Imam Wibowo (Jurnal Ekonomi dan Industri, 2025)
The purpose of this study is to analyze the influence of leadership, organizational culture, on career development through employee job satisfaction at PT. Tasa Tritama Utama In this study using the analysis of leadership paths and organizational culture on career development The results of the study indicate that job satisfaction has a positive influence on career development, both directly and indirectly, both partially and simultaneously. This means that job satisfaction is a key factor that mediates the influence of leadership and organizational culture on career development. Improving employee job satisfaction at PT Tasa Tritama Utama can be an effective strategy to encourage their career development, both through direct effects and by improving the quality of leadership and existing organizational culture.